2009
DOI: 10.1038/modpathol.2009.99
|View full text |Cite
|
Sign up to set email alerts
|

Glial fibrillary acidic protein in tumor types with cartilaginous differentiation

Abstract: Glial fibrillary acidic protein (GFAP) is a member of the intermediary filament protein family. It is an important component of astrocytes and a known diagnostic marker of glial differentiation. GFAP is expressed in other neural tumors and pleomorphic adenoma and, less frequently, in cartilage tumors, chordomas, and soft tissue myoepitheliomas. The aim of this study was to evaluate the role of GFAP and its reliability in nonglial tumors as an immunohistochemical marker. We evaluated GFAP gene and protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 16 publications
1
17
0
Order By: Relevance
“…Osteosarcomas are vascular, but the Finally, dexamethasone induced cells expressing markers unique to the endodermal phenotype, hepatocytes. Our results are consistent with those of other studies of nonosteoblast phenotypes, including some ectodermal phenotypes, in osteosarcomas in vivo [2,8,12,23,27,30,39,40,45,46,49]. However, no studies have reported the presence of staining in osteosarcomas in vivo for neurons, oligodendrocytes, skeletal muscle, or adipocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Osteosarcomas are vascular, but the Finally, dexamethasone induced cells expressing markers unique to the endodermal phenotype, hepatocytes. Our results are consistent with those of other studies of nonosteoblast phenotypes, including some ectodermal phenotypes, in osteosarcomas in vivo [2,8,12,23,27,30,39,40,45,46,49]. However, no studies have reported the presence of staining in osteosarcomas in vivo for neurons, oligodendrocytes, skeletal muscle, or adipocytes.…”
Section: Discussionsupporting
confidence: 93%
“…As for moesin, it is a member of the ERM (ezrin, radixin, moesin) protein family and connects major cytoskeletal structures to the plasma membrane. It has been proved that ERM is activated by phosphorylation in OS [23] and ezrin, another member of ERM, is believed to involve in matastatsis in osteosarcoma [24]. It is suggested that ezrin and, potentially, other members of the ERM (ezrin-radixin-moesin) family have key roles in the coordination of signals and cellular complexes that are required for the successful metastasis of these and other malignancies [24].…”
Section: Discussionmentioning
confidence: 99%
“…GFAP overexpression is an important signs of Ast proliferation when central nervous system is injury. Rats with impairment memory whose Ast hypertrophy and neuronal loss, which shows there are a certain relationship between GFAP-positive cell and impaired memory [5] .…”
Section: B the Concentrations Of Il-1β、il-6、tnf-αmentioning
confidence: 97%